Prediction Models for the Phenolic Contents in Some Hypericum Species from Turkey - Serhat Odabas, Mehmet; Radusiene, Jolita; Cirak, Cuneyt; Camas, Necdet (Asian Journal of Chemistry, 2010)
In this research, models for prediction of the content of several phenolics namely chlorogenic acid, hyperoside, apigenin-7-O-glucoside, rutin, quercitrin, quercetin and viteksin were developed for Hypericum originafolium Willd, Hypericum perfoliatum L. and Hypericum montbreii Spach. growing in Northern Turkey. Wild growing plants were harvested at vegetative, floral budding, full flowering, fresh fruiting, mature fruiting stages and dissected into stem, leaf and reproductive tissues. Actual phenolic content of plant materials was measured by high performance liquid chromatography method. Multiple regression analysis with Excel 2003 computer package program was performed for each species and phenolic separately to develop the models. The produced equation for predicting of phenolic content in different tissues of the species was formulized as: PC= [a + (b1 × S) + (b2 × L) + (b3 × R) + (b4 × S2) + (b5 × (1/RP))] where PC is whole plant content of phenolic compound, S is phenolic content of stem, L is phenolic content of leaf, RP is phenolic content of reproductive parts and a, b1, b2, b3, b4 and b5 are coefficients. R2 values varied between 0.65-0.99 for H. originafolium, 0.67- 0.99 for H. perfoliatum and 0.96-0.99 for H. montbreii depending of the phenolics examined. All R2 values and standard errors were found to be significant at the p < 0.05 level.